2009
DOI: 10.1186/1471-230x-9-30
|View full text |Cite
|
Sign up to set email alerts
|

Detection of serum MMP-7 and MMP-9 in cholangiocarcinoma patients: evaluation of diagnostic accuracy

Abstract: Background: Cholangiocarcinoma is an aggressive tumor with a tendency for local invasion and distant metastases. Timely diagnosis is very important because surgical resection (R0) remains the only hope for a cure. However, at present, there is no available tumor marker that can differentiate cholangiocarcinoma from benign bile duct disease. Previous studies have demonstrated that matrix metalloproteinase (MMP)-7 and MMP-9 are frequently expressed in cholangiocarcinoma specimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 28 publications
(37 reference statements)
5
38
2
Order By: Relevance
“…1. All four assays are capable of reliable measurements below the cut-off values established for healthy individuals and reported in literature: CA125 35U/mL (12), HE4 40–85pM (age-dependent) (39), CA72-4 8.5U/mL (40) and MMP-7 7.4ng/mL (41). Reliable measurements of biomarker concentrations below cut-off levels are essential for establishing baselines for longitudinal biomarker monitoring.…”
Section: Resultsmentioning
confidence: 80%
“…1. All four assays are capable of reliable measurements below the cut-off values established for healthy individuals and reported in literature: CA125 35U/mL (12), HE4 40–85pM (age-dependent) (39), CA72-4 8.5U/mL (40) and MMP-7 7.4ng/mL (41). Reliable measurements of biomarker concentrations below cut-off levels are essential for establishing baselines for longitudinal biomarker monitoring.…”
Section: Resultsmentioning
confidence: 80%
“…11,12 Other markers may have clinical significance. Serum levels of matrix metalloproteinase-7 13 and tumour M2-PK 14 have been shown to have the potential to differentiate CCA from benign biliary tract disease with more sensitivity and specificity than CA19-9. In addition, an animal trial reported that a novel CCA-associated carbohydrate antigen may have potential as a marker for the early diagnosis of CCA.…”
Section: Diagnosismentioning
confidence: 99%
“…Leelawat, Sakchinabut, Narog, and Wannaprasert analyzing the CEA, CA 19.9, MMP-7 and MMP-9 serum levels in patients with cholangiocarcinoma detected that only MMP-7 level was considerably higher in patients with cancer (25). Levels of total MMP-7 can be measured in human serum and it is feasible using a simple ELISA technique, as this has been recently shown in few other studies.…”
Section: Discussionmentioning
confidence: 99%